Litopenaeus vannamei stylicins are constitutively produced by hemocytes and intestinal cells and are differentially modulated upon infections. Issue 86 (March 2019) - Farias, Natanael Dantas; Falchetti, Marcelo; Matos, Gabriel Machado; Schmitt, Paulina; Barreto, Cairé; Argenta, Nicolas; Rolland, Jean-Luc; Bachère, Evelyne; Perazzolo, Luciane Maria; Rosa, Rafael Diego
Abstract: Stylicins are anionic antimicrobial host defense peptides (AAMPs) composed of a proline-rich N-terminal region and a C-terminal portion containing 13 conserved cysteine residues. Here, we have increased our knowledge about these unexplored crustacean AAMPs by the characterization of novel stylicin members in the most cultivated penaeid shrimp, Litopenaeus vannamei . We showed that the L. vannamei stylicin family is composed of two members ( Lvan -Stylicin1 and Lvan -Stylicin2) encoded by different loci which vary in gene copy number. Unlike the other three gene-encoded antimicrobial peptide families from penaeid shrimp, the expression of Lvan -Stylicins is not restricted to hemocytes. Indeed, they are also produced by the columnar epithelial cells lining the midgut and its anterior caecum. Interestingly, Lvan -Stylicins are simultaneously transcribed at different transcriptional levels in a single shrimp and are differentially modulated in hemocytes after infections. While the expression of both genes showed to be responsive to damage-associated molecular patterns, only Lvan -Stylicin2 was induced after a Vibrio infection. Besides, Lvan -Stylicins also showed a distinct pattern of gene expression in the three portions of the midgut (anterior, middle and posterior) and during shrimp development. We provide here the first evidence of the diversity of the stylicin antimicrobial peptide family in terms of sequence and gene expression distribution and regulation. Highlights: Stylicins from L. vannamei are composed of two members, Lvan -Stylicin1 and -2. Lvan -Stylicins are encoded by separate genes and transcribed at different levels. Lvan -Stylicins are expressed in hemocytes and in midgut epithelial cells. Expression of Lvan -Stylicins is differentially modulated in response to infections.